Corporate governance and corporate failure in the context of agency theory / Azlinda Mohamad, Faizah Darus and Rohayati Jusoh - Mohamad, Azlinda; Darus, Faizah; Jusoh, Rohayati (2011)
Corporate failure involves the cessation of trading or activity of a business, which is generally preceded by financial distress. Poor corporate governance has been identified as one of the factors that contribute to corporate failure. As an effort to prevent corporate failures, corporate governance reforms have been undertaken worldwide in an attempt to improve corporate governance. This is because a good governance structure would ensure that the roles and responsibilities of stakeholders and management would be well defined and strictly adhered to. This study aims to investigate the impact of corporate governance mechanisms on financially distressed companies which is proxied by PN4 and PN17 status (Practice Note 4 and Practice Note 17) of Malaysian public listed companies for a three year period from 1 January 2004 to 31 December 2006. In general, the aim of this study is to increase the understanding and to provide new empirical evidence of the impact of corporate governance attributes on the poor performance of companies in Malaysia and to test the robustness of the agency theory in the context of corporate governance. The research is concerned with three corporate governance mechanisms: board structure, ownership structure and internal control. The results of this study provide evidence that there is a significant negative association between CEO duality and financial distress condition. This implies that leadership structure affects the performance of companies. The findings suggest that CEO duality will reduce agency problem as the agent will act in his best interest since he can provide better strategic vision in the companies’ goals and objectives. Other governance and internal control mechanisms identified in the study were found to be insignificant.